Cuerpos intimidados: secuelas somáticas del terrorismo de Estado en La fiesta del Chivo de Mario Vargas Llosa - Sawala, Wojciech (Studia Romanica Posnaniensia, 2015)
This paper argues that Mario Vargas Llosa’s novel The Feast of the Goat (2000) uses the images of the bodies of three of its characters (Urania Cabral, Trujillo and Agustín Cabral) to represent the mechanisms of state terrorism at the time of Trujillo’s dictatorship in the Dominican Republic. It is a traumatizing system, which leaves somatic marks in all the actors involved. We analyze the manners in which the Peruvian author uses the images of protagonists’ organic processes to sketch the psychical, emotional and ideological processes and states, linked to or generated by the policies of intimidation.